2014
DOI: 10.2217/imt.14.77
|View full text |Cite
|
Sign up to set email alerts
|

Plant Components for Immune Modulation Targeting Dendritic Cells: Implication for Therapy

Abstract: Medicinal plant utilization is as old as human life. There are thousands of herbs consumed for medicinal purposes all over the world, especially in east. Their value has not decreased over time and many modern pharmaceuticals have originated from traditional medicinal plants. Studying the reason for their influence is an attractive field of medicine. Among various types of herbs, some function via their immunomodulatory effects. Experiments have shown the regulatory influences of several plants on each type of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…Considering that leishmaniasis depends on the host's immune response for effective healing, Leishmania pathogens can directly interfere with protein synthesis in the host and innate inhibitory responses to evade mechanisms of cell death. The intracellular localization of the pathogen can also impact the activity of antileishmanial drugs, in addition to their ability to be internalized by host cells, affect the rate of uptake, resist intracellular degradation and trafficking, and possibly cause cytotoxicity . Thus, we also investigated the modulatory effects of TrEO on cytokine production by murine cells that were infected with Leishmania spp.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that leishmaniasis depends on the host's immune response for effective healing, Leishmania pathogens can directly interfere with protein synthesis in the host and innate inhibitory responses to evade mechanisms of cell death. The intracellular localization of the pathogen can also impact the activity of antileishmanial drugs, in addition to their ability to be internalized by host cells, affect the rate of uptake, resist intracellular degradation and trafficking, and possibly cause cytotoxicity . Thus, we also investigated the modulatory effects of TrEO on cytokine production by murine cells that were infected with Leishmania spp.…”
Section: Resultsmentioning
confidence: 99%
“…Polysaccharides isolated from Astragalus membranaceus , Ganoderma lucidum and Radix ophiopogonis have decreased CD40 expression but not CD80/CD86 in dendritic cells [ 27 ]. Further, a review based on the immune modulation of plants targeting dendritic cells [ 28 ] has identified that Azadirachta indica upregulated CD40, CD83, CD80 and CD86 [ 29 ], Astragalus increased the expression of CD40, CD80 and CD86 [ 30 ], garlic elevated CD40 levels but not CD86 [ 31 ], curcumin inhibited the expression of CD80 and CD86 [ 32 ], Plantago asiatica increased levels of CD80 and CD86, Corydalis bungeana decreased the expression of CD40 & CD86 and Licorice root significantly suppressed the expression of CD80 and CD86 in Dendritic cells [ 28 ]. Though there are multiple studies available on the effect of medicinal plants on the expression of co-stimulatory molecules such as CD80, CD83, CD86 and CD40 on dendritic cells, studies on cell type such as lymphocytes are limited.…”
Section: Discussionmentioning
confidence: 99%
“…The dried whole plant, also known in traditional Chinese medicine (TCM) as C. bungeana Herba can be traced back to Tang Dynasty, and has been officially listed in the Chinese Pharmacopeia . Traditionally, C. bungeana Turcz has long been used in China, Japan, Korea, and other Eastern Asian countries for the treatment of different ailments such as hordeolum , icteric hepatitis , and haemorrhoids . Modern pharmacological studies have shown that C. bungeana Turcz is a rich source of isoquinoline alkaloids with various biological properties including anti‐inflammatory , antinociceptive , antibacterial , and other related activities.…”
Section: Introductionmentioning
confidence: 99%